2006
DOI: 10.1002/bip.20586
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of normal, benign, and malignant breast tissues by Raman spectroscopy

Abstract: Breast cancers are the leading cancers among females. Diagnosis by fine needle aspiration cytology (FNAC) is the gold standard. The widely practiced screening method, mammography, suffers from high false positive results and repeated exposure to harmful ionizing radiation. As with all other cancers survival rates are shown to heavily depend on stage of the cancers (Stage 0, 95%; Stage IV, 75%). Hence development of more reliable screening and diagnosis methodology is of considerable interest in breast cancer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 19 publications
5
100
0
1
Order By: Relevance
“…These training sets were challenged by large testing data from certified 6,21 as well as 69 (427 spectra) blinded specimen. 6,22 Typical spectra of established Raman models of normal, malignant and benign breast tissues are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These training sets were challenged by large testing data from certified 6,21 as well as 69 (427 spectra) blinded specimen. 6,22 Typical spectra of established Raman models of normal, malignant and benign breast tissues are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…8,23 In our earlier studies, a total of 258 sites/spectra (105 normal, 101 malignant, 52 benign) were recorded on histopathologically certified 29 normal, 24 infiltrating ductal carcinoma and seven fibroadenoma breast tissues. 21 Among them, randomly selected 36 normal, 35 malignant, and 21 benign breast tissue spectra were used for development of spectroscopic models. These models were then verified and evaluated by 69 blinded samples.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…A widely used MVA method to analyze Raman spectra is PCA, because it is readily implemented in most standard software packages for data acquisition and data analysis. [32][33][34] A comprehensive review of PC analysis of Raman spectra can be found elsewhere. 35 PCA applies a set of linear-orthogonal transformations to the data set, which identifies correlated variables in the data and assigns them to new, uncorrelated variables, the socalled PCs.…”
Section: Fig 2 (A)mentioning
confidence: 99%